Electrochemical safety assessment of Magnetite nanoparticles: utilizing cyclic voltammetry for alternative biogenic MRI contrast media - Ab Hamid, Suzana; Al-shimmari, Haydar Abdulkadeer Taheer; Suppiah, Subapriya; Radhi, Muhammed Mizher; A. Kadhim, Duha; A. Abid, Muslim (Medico Legal Society, 2024)
Magnetic resonance imaging (MRI) is a extensively used as diagnostic imaging technique that depend on the magnetic properties of atoms within the body. There is interest in finding alternative contrast media, like iron oxide nanoparticles, that may have improved properties compared to gadolinium agents. Iron oxide nanoparticles (IONPs) are a promised alternative result as their superparamagnetic conductance, low toxicity, and biocompatibility. Cyclic voltammetry (CV) is an electroanalytical mechanization used to explore the redox behavior of materials. CV was applied to study the electrochemical properties of IONPs and their potential as a safer alternative MRI contrast agent. Experiments were conducted using a three-electrode system in CV (potential-stat) with the IONPs in blood medium. The oxidation transitions in the magnetite structure were studied. The peak separation and peak current values provided insights into the electron transfer kinetics and electrochemical activity of the IONPs. The electrochemical results proved the redox activity and reversibility of the Fe3O4 NPs, articulating their potential as MRI contrast agents. The spotted redox behavior was attributed to the unique electronic structure and magnetic properties of the nanoparticles. The CV data provided valuable information about the electron transfer processes and charge storage capabilities of the IONPs, which are important for their use in MRI applications. This electrochemical characterization of ionic diffusivities in blood medium at different concentrations, scan rates, pH, and ascorbic acid as the influent, where the ionic diffusivities are comprehensively adopted as alternative contrast agents in MRI. This lectrochemical study explores the role of ionic diffusivities in enhancing electron transport kinetics, further supportive iron oxide nanoparticles as a promising alternate to gadolinium-based contrast agents for MRI applications.